2019
DOI: 10.1111/imr.12741
|View full text |Cite
|
Sign up to set email alerts
|

Extrafollicular responses in humans and SLE

Abstract: Summary Chronic autoimmune diseases, and in particular Systemic Lupus Erythematosus (SLE), are endowed with a long‐standing autoreactive B‐cell compartment that is presumed to reactivate periodically leading to the generation of new bursts of pathogenic antibody‐secreting cells (ASC). Moreover, pathogenic autoantibodies are typically characterized by a high load of somatic hypermutation and in some cases are highly stable even in the context of prolonged B‐cell depletion. Long‐lived, highly mutated antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
204
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 222 publications
(218 citation statements)
references
References 127 publications
(196 reference statements)
6
204
1
7
Order By: Relevance
“…The emergence of CD11c + DN B cells is not unique to active SLE, and even healthy subjects display this B cell subset in the blood and tonsil albeit at a lower frequency [12,14,18,27,29] Jenks et al showed that this pathway was strongly activated by the combination of the signals by BCR, TLR7-ligand, IL-21, and IFN-γ, and TLR7-ligand was the most critical factor among those [13]. By contrast, Wang et al showed that BCR and CD40 signals were sufficient to induce human naïve B cells to differentiate into CD11c + DN B cells, and the supplementation of IL-21 strongly enhanced the differentiation.…”
Section: Development Of Cd11c + Dn B Cells In Human Slementioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of CD11c + DN B cells is not unique to active SLE, and even healthy subjects display this B cell subset in the blood and tonsil albeit at a lower frequency [12,14,18,27,29] Jenks et al showed that this pathway was strongly activated by the combination of the signals by BCR, TLR7-ligand, IL-21, and IFN-γ, and TLR7-ligand was the most critical factor among those [13]. By contrast, Wang et al showed that BCR and CD40 signals were sufficient to induce human naïve B cells to differentiate into CD11c + DN B cells, and the supplementation of IL-21 strongly enhanced the differentiation.…”
Section: Development Of Cd11c + Dn B Cells In Human Slementioning
confidence: 99%
“…The emergence of CD11c + DN B cells is not unique to active SLE, and even healthy subjects display this B cell subset in the blood and tonsil albeit at a lower frequency . The differentiation mechanism by which resting naïve B cells become activated and differentiate into CD11c + DN B cells in humans is currently under extensive investigation.…”
Section: Introductionmentioning
confidence: 99%
“…38 It is important to emphasize that the contribution of these well-defined mechanisms have been overwhelmingly assessed within the normal GC environment. Yet, the emergence of tertiary lymphoid organ (TLO) formation 39 and extrafollicular response pathways 40 as critical features of autoimmunity demand a broader look at peripheral tolerance control mechanisms. Indeed, TLO formation has become a centerpoint in tissue-specific autoimmune development, and dysregulated TLO formation has now been positively identified in diverse human autoimmune disorders including Sjögren's syndrome, myasthenia gravis, multiple sclerosis, rheumatoid arthritis, and SLE.…”
Section: G Erminal Center Checkp Oints and Toler An Ce Enforcementmentioning
confidence: 99%
“…18 Although mouse ABCs and human atypical MBCs are phenotypically similar they appear to have distinct functional profiles. [19][20][21] Moreover, at this point in time we do not yet understand the relationships between atypical MBCs in various chronic infectious diseases. 18 In this regard mouse ABCs appear to be more closely related to T-bet + B cells in human and mouse autoimmune disease rather than atypical MBCs in human chronic infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…18 In this regard mouse ABCs appear to be more closely related to T-bet + B cells in human and mouse autoimmune disease rather than atypical MBCs in human chronic infectious diseases. [19][20][21] Moreover, at this point in time we do not yet understand the relationships between atypical MBCs in various chronic infectious diseases. Consequently, in this review, focused on the impact of chronic infectious diseases on the MBC compartment, we restrict our discussion primarily to human atypical MBCs in malaria.…”
Section: Introductionmentioning
confidence: 99%